2017
DOI: 10.1371/journal.pone.0175126
|View full text |Cite
|
Sign up to set email alerts
|

Trunk kinematics and low back pain during pruning among vineyard workers—A field study at the Chateau Larose-Trintaudon

Abstract: The prevalence of low back disorders is dramatically high in viticulture. Field measurements that objectively quantify work exposure can provide information on the relationship between the adopted trunk postures and low back pain. The purposes of the present study were three-fold (1) to carry out a kinematics analysis of vineyard-workers’ pruning activity by extracting the duration of bending and rotation of the trunk, (2) to question separately the relationship between the duration of forward bending or trunk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…MoCap techniques for industrial applications were primarily used for the assessment of health and safety risks in the working environment ( Table 6 , 64.4%), whilst fatigue and proper posture were the most targeted issues [ 48 , 49 , 72 ]. The research interest of the industry in health and safety MoCap applications increased steadily over the reviewed period ( Figure 3 , right).…”
Section: Resultsmentioning
confidence: 99%
“…MoCap techniques for industrial applications were primarily used for the assessment of health and safety risks in the working environment ( Table 6 , 64.4%), whilst fatigue and proper posture were the most targeted issues [ 48 , 49 , 72 ]. The research interest of the industry in health and safety MoCap applications increased steadily over the reviewed period ( Figure 3 , right).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies suggest to utilise measures of the kinematics of the trunk (Balaguier et al 2017;LagerstedOlsen et al 2016;Lunde et al 2017;Robert-Lachaine et al 2017;Villumsen et al 2016) or a combination of these methods (Samani et al 2012). So far, most studies based on in situ assessments have studied bending and torsion of the trunk but have not provided assessments of the physical loads (Balaguier et al 2017;Villumsen et al 2015Villumsen et al , 2016. The current body of literature reinforces the need for direct objective measures enabling delineation of lifts with low or high risk of contracting low back injuries.…”
Section: Kinematicsmentioning
confidence: 99%
“…On the contrary, in health sector workers, the amount of sitting time is inversely related with lumbar pain intensity [152]. In another working area, results reported in [153] showed that grape-pruning activity leads to the adoption of curved and forward folded trunk postures inducing a significant risk of lumbar musculoskeletal disorders.…”
Section: Physical Activity As a Predictor Of Painmentioning
confidence: 99%
“…This scenario justifies current efforts for the development of objective physical activity evaluation systems for the identification of pain-related activities (breast pain, headache, etc.) [137,138], for the evaluation of pain intensity [139][140][141][142][143][144][145][146][147], for the detection of postures, movements or activities that can produce pain [148][149][150][151][152][153], or for the improvement of quality of life and a reduction of pain intensity [154][155][156][157][158].…”
Section: Accelerometry-based Activity Evaluation and Chronic Painmentioning
confidence: 99%